2017
DOI: 10.1016/j.jss.2017.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Variation in readmission expenditures after high-risk surgery

Abstract: Background The Hospital Readmissions Reduction Program reduces payments to hospitals with excess readmissions for three common medical conditions and recently extended its readmission program to surgical patients. We sought to investigate readmission intensity as measured by readmission cost for high-risk surgeries and examine predictors of higher readmission costs. Materials and Methods We used the Healthcare Cost and Utilization Project's State Inpatient Database to perform a retrospective cohort study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Data are stratified by discharge destination (ie, to home or to a facility) and are adjusted for procedure type, age, sex, race, Charlson score, preadmission disposition, and calendar year. pancreatectomy) and found that 19.4% of patients were discharged to a skilled nursing facility, 3 which is similar to the rate of 22.8% found in this study. Another study looked at 30-day readmission intensity in cystectomy patients using Surveillance, Epidemiology, and End Results-Medicare data and found that 77% of readmissions occurred within the first week of discharge.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Data are stratified by discharge destination (ie, to home or to a facility) and are adjusted for procedure type, age, sex, race, Charlson score, preadmission disposition, and calendar year. pancreatectomy) and found that 19.4% of patients were discharged to a skilled nursing facility, 3 which is similar to the rate of 22.8% found in this study. Another study looked at 30-day readmission intensity in cystectomy patients using Surveillance, Epidemiology, and End Results-Medicare data and found that 77% of readmissions occurred within the first week of discharge.…”
Section: Discussionsupporting
confidence: 88%
“…The existing literature is mainly limited to 30‐day readmissions and to initial hospital discharge destination following these high‐risk cancer surgeries. One study using data from the Healthcare Cost and Utilization Project's State Impatient Database examined patients undergoing similarly high‐risk abdominal surgery (including open abdominal aortic aneurysm repair, cystectomy, esophagectomy, and pancreatectomy) and found that 19.4% of patients were discharged to a skilled nursing facility, which is similar to the rate of 22.8% found in this study. Another study looked at 30‐day readmission intensity in cystectomy patients using Surveillance, Epidemiology, and End Results‐Medicare data and found that 77% of readmissions occurred within the first week of discharge .…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…abdominal aortic aneurysm repair, cystectomy, oesophagectomy, and pancreatectomy), based on analyses of inpatient databases for NY, IA, NC, and WA states in USA. 16 Furthermore, Wilbur and colleagues 13 reported a mean cost of $25 416 per readmission (total readmission-related costs during the study period were $4 523 959). Based on these reports, sugammadex may yield considerable economic benefits despite the higher direct costs of reversing moderate rocuronium-induced NMB with sugammadex compared with neostigmine.…”
mentioning
confidence: 99%